Nonlinear dynamics characteristics and influence factors analysis of servo hydraulic cylinder. (October 2018) - Li, Jun; Li, Huanliang; Cui, Hongxin; Zhu, Yawei
Aiming at problems of vibration, impact, and noise, the nonlinear dynamic characteristics of servo hydraulic cylinder are studied by using combination of theoretical derivation and simulation experiment methods. The nonlinear effect rules of spring force and friction force are analyzed based on nonlinear dynamic theory; it can be derived that the coupling effect rules of nonlinear spring force and friction force can be described by Duffing–Van Der Pol equation. The dynamic simulation model of servo hydraulic cylinder is established by using SimHydraulics software. The numerical simulation and experiment results showed that nonlinear vibration of servo hydraulic cylinder is mainly caused by exciting force, spring force, and friction force; the system has different motion states when the parameters take different values, which lays a good foundation for the optimal designs and precise control of hydraulic cylinder.